Effect of overexpression of Arabidopsis thaliana SHB1 and KLUH genes on seed weight and yield contributing traits in Indian mustard (Brassica juncea L. (Czern.)) - Savadi, Siddanna; Naresh, Vasupalli; Kumar, Vajinder; Dargan, Seema; Gupta, Navin Chandra; Chamola, Rohit; Bhat, Shripad Ramachandra (The Indian Journal of Genetics and Plant Breeding, 2016)
Seed size is a highly heritable trait in mustard and increasing seed size could improve crop productivity. Here we report the effect of overexpression of two Arabidopsis genes SHB1 and KLUH on seed weight and other yield contributing traits in Brassica juncea. KLUH gene was expressed under its own promoter, whereas the constitutive HPL promoter drove SHB1. Transgenic status was confirmed through PCR, RT-PCR and Southern analyses. The three SHB1 events contained single copy of transgene, whereas 12 KLUH events carried 1-4 copies of transgenes. All transgenics were fertile and comparable to non-transgenic counterpart for most of the agronomic traits in both T0 and T1 generations. Seed size and seed weight in SHB1 transgenics were 30-40% higher than the control, whereas one KLUH event showed significant increase in seed weight. Constitutive overexpression of SHB1 in B. juncea had undesirable pleiotropic effects that were comparable to the Arabidopsis lines overexpressing IKU2.